KAJIAN STRUKTURALISME GENETIK: PANDANGAN DUNIA DALAM TIGA CERPEN PADA KUMPULAN CERPEN DECEPTION KARYA ROALD DAHL - Fitri Dyah Kirana (Nusantara Hasana Journal, 2023)
This study aims to describe the human facts and collective subjects to reveal the author's worldview in three short stories contained in the collection of short stories Deception by Roald Dahl. All three short stories have the same theme, namely lies. The three short stories analyzed were (1) My Lady Love, My Dove (2) The Mildenhall Treasure (3) Lamb to the Slaughter. This study used a descriptive qualitative approach. The approach is used using the theory of genetic structuralism with a dialectical method. The results showed that human facts were found in the form of social activities, and cultural creations. The collective subject is divided into two, namely the upper social class and the lower social class. The author's worldview expressed by Roald Dahl as a part of collective subject found in the three stories is a hypocritical view. Dahl through selected stories depict how human lie to achieve their needs and how the appearance can be very deceptive.